(untitled) (Journal of Comparative & International Higher Education, 2022)
Global competition is currently reshaping higher education worldwide. Hungarian and Chinese higher education institutions are increasingly channeling resources to higher education development to promote the internationalization of higher education. There have been few studies specified differences between Hungarian and Chinese higher education internationalization. Over the past few years, both Hungarian and Chinese governments have started to prioritize raising international student mobility to enhance countries’ competitiveness at the global level. This article outlines the definition of higher education internationalization to provide a comprehensive understanding of this term. This article also briefly describes the background of higher education in Hungary and China and compares determinants of higher education internationalization between the two countries, particularly focusing on the context of international student mobility. This article summarizes and compares higher education internationalization indicators between Hungary and China. This article contributes to a better understanding of the development of higher education internationalization in Hungary and China.